Features of immune status in COVID-19 convalescents - Alina S. Shkaberda; Elena A. Kordovskaya; Diana Yu. Bakuta; Lyubov I. Plotnichenko; Alexander A. Gorbunov; Leya E. Sorokina (Russian Open Medical Journal)
Study objective — assessment of the humoral and cell-mediated immunity features in COVID-19 convalescents three months after their discharge from the hospital. Material and Methods — The study involved 78 COVID-19 convalescents who, depending on the profile of specific IgM and IgG antibodies to SARS-CoV-2, were divided into three groups. The control group consisted of 50 volunteers. Detection of IgM and IgG in blood serum was performed by ELISA. Determination of CRP concentration was conducted using the immunoturbidimetric assay. To determine the levels of IL-6, a sandwich version of the solid-phase ELISA was employed. Immunophenotyping of lymphocytes was performed via flow cytometry. Results — Of 78 COVID-19 convalescents three months after their discharge from the hospital, 30.8% of them had a profile of specific antibodies IgM(+)IgG(+), 37.2% had IgM(-)IgG(+), and 32.0% were characterized by IgM(-)IgG (-). COVID-19 convalescents with an IgM(-)IgG(-) profile had the highest levels of NK cells, T helper cells, B lymphocytes (p<0.001) and were characterized by hyperproduction of proinflammatory IL-6 (p<0.001). COVID-19 convalescents with an IgM(+)IgG(+) specific antibody profile were characterized by the highest levels of cytotoxic T lymphocytes (p<0.001). In a COVID-19 convalescent with an IgM(-)IgG(+) specific antibody profile, we observed an increase in the number of lymphocytes expressing late activation/apoptosis molecules (p<0.001). Conclusion — The collected data is of potential importance in clinical practice for developing a prognosis for epidemiological situation development, as well as for planning preventive measures to COVID-19.